Influência do teor de argila nas propriedades térmicas, mecânicas e morfológicas de filmes de poli (álcool vinílico) (PVOH) com nanocristais de celulose (CNC) - Araújo, Tamíris Rodrigues da Silva (2019)
In this work were obtained nanocomposites films of polyvinyl alcohol (PVOH), glycerol, cellulose nanocrystals (CNC) and montmorillonite clay (MMT). The aim was to study the effect of the addition of both MMT and CNC clay on the morphological, thermal and mechanical properties of the PVOH polymer matrix, varying the MMT content at 0, 10, 20, 30 and 40% w/w setting the concentration of CNC at 3% w/w. The films were prepared by solvent evaporation and further characterized by X-ray diffraction, Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and tensile strength. FTIR results showed interaction between PVOH, CNC and MMT functional groups. DSC results showed that the addition of clay inhibited the crystallization of PVOH, making it completely amorphous with the incorporation of clay in contents above 30% w/w. The thermal stability of PVOH / NCC nanocomposite was elevated with MMT incorporation at two different steps of degradation. Moreover, the increase of MMT content above 20% w/w in the nanocomposites resulted in increased tensile strength and elastic modulus of the polymer matrix, which was consolidating with the absence of agglomerates and voids in the reinforcement/polymer matrix interface observed in SEM images. In addition, the films showed flexibility even with the presence of high clay contents due to the use of glycerol as plasticizer. Finally, the results presented in this paper suggest that films made with the combination of PVOH, glycerol, CNC and MMT clay may be an alternative for the production of biodegradable films with high mechanical properties.